Examination of the Correlation Between the Happiness and Psychological Well-Being Levels of the Exercisers(Diyarbakır Province) - Nurdan Ateş (Selcuk University, 2023)
In this study, it is aimed to determine the relationship between these two variables by examining the happiness and psychological well-being levels of individuals who exercise in terms of different variables. The sample group of the research consists of 232 individuals, 159 women and 73 men, who exercise in the sports centers in Diyarbakir. Oxford Happiness Scale and Psychological Well-Being Scale were used as data collection tools. Parametric tests were applied due to the normal distribution of the data. Post-Hoc tests were used to determine the direction of the difference. In addition, Pearson Correlation analysis was used to determine the relationship between happiness and psychological well-being of individuals who exercise. The significance level was determined as .05. According to the findings obtained in the study, it was determined that the happiness and psychological well-being levels of the individuals who exercised were above the medium level. It has been observed that the happiness and psychological well-being levels of the individuals who exercise do not differ according to the age and gender variable. While a difference was observed in favor of those participating in social activities in the psychological well-being levels of individuals participating in social activities, no significant difference was observed in terms of happiness levels. Among the self-defining situations of individuals who exercise in daily life, it was observed that those who were peaceful were happier than those who were stressed, while those who were calm and peaceful had higher levels of psychological well-being than those who were stressed. As a result, it has been observed that there is a moderate, positive relationship between the happiness levels of the individuals who exercise and their psychological well-being levels.